2019
DOI: 10.31234/osf.io/6azqs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personality and Morality: Role of the Big Five Personality Traits in Predicting the Four Components of Moral Decision Making

Abstract: Introduction: The aim of the present study was to investigate the predicting role of the big five personality traits in the four components of moral decision-making. Method: The population of this descriptive-correlation study included all the students in the University of Mazandaran. The participants were 384 students selected by stratified random sampling. In order to collect data, the Mini-IPIP, Ethical Sensitivity Scale, DIT-2, Moral Identity Questionnaire and the Moral Courage Scale were used. The data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The results of Abbasi-Asl and Hashemi's research indicated that conscientiousness, which is one of the dimensions of the five-factor model of personality, is related to moral courage. It is clear that the individual who is responsible and follows the organizational rules and values, has more moral courage, because the basic characteristic of moral courage is to continue to do the right thing [22]. Conscientious nurses feel more responsible for doing good things.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Abbasi-Asl and Hashemi's research indicated that conscientiousness, which is one of the dimensions of the five-factor model of personality, is related to moral courage. It is clear that the individual who is responsible and follows the organizational rules and values, has more moral courage, because the basic characteristic of moral courage is to continue to do the right thing [22]. Conscientious nurses feel more responsible for doing good things.…”
Section: Discussionmentioning
confidence: 99%
“…Conscientiousness and responsibility of nurses are essential for doing the right thing. On the other hand, insistence on doing the right thing is one of the basic characteristics of moral courage [22].…”
Section: Introductionmentioning
confidence: 99%
“…Political ideologies likely shape behaviors deemed moral or immoral. Given that conscientiousness and persistence, common correlates of grit, are often associated with moral decisions (Abbasi‐Asl & Hashemi, 2019) and ideologies are often linked to constructs such as conscientiousness and consistency, we examine the relationships between political ideology and grit on moral consumer decisions.…”
Section: Political Ideologymentioning
confidence: 99%
“…Higher openness (Özbağ, 2016) and neuroticism (Decuypere et al, 2018) are found to be positively associated with ethical behavior and moral obligations. Agreeableness, openness, and conscientiousness are positively related to moral identity, agreeableness is positively related to moral sensitivity, and conscientiousness is positively related to moral courage (Abbasi‐Asl & Hashemi, 2019). Openness, conscientiousness, agreeableness, and neuroticism positively relate to moral reasoning (Athota et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%